KOMPONEN KERAGAMAN SIFAT-SIFAT YANG BERHUBUNGAN DENGAN KETAHANAN TERHADAP PENGGEREK POLONG (Etiella inckenella Treitschke) PADA TANAMAN KEDELAI (Glycine max L. Merril) - Candra, Agung; Rasyad, Aslim; Salbiah, Desita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
One of main problems in increasing soybean production is the attack of pests such as soybean  pod borer  (Etiella zinckenella Treitschke). The objectives of this research was to determine the variance components and heritability of various characters associated with resistance to soybean  pod borer. A field experiment was established by randomized complete block design where six cultivars of soybean including Gema, Grobogan, Kaba, Willis, lines KM 19 and KM 25 are planted in plots of  2.5 m in length and 2 m in wide. The experiment  was conducted at the Center for Integrated Seed production at Pasir Pengaraian, Riau  Province. The parameters observed were number of larva per plant, percentage of damage pods per plant, percentage of damage seeds per plant, number of pods per plant, number of seeds per plant, yield per m2, weight of 100 seeds dry and additional observations. The data were analyzed by using analysis of variance and then the components of genetic and phenotypic variance and heritability were calculated. The results showed that all parameters were relatively narrow genetic variation. Phenotypic variation was narrow for number of larva per plant, percentage of attacked pods and  weight of 100 seed dry, and considered wide for the percentage of seeds damage, number of filled pods, number of seeds per plant, and yield per m2.  Broad sense heritability values were high for percentage of attacked pods, the percentage of seeds damage, number of filled pods, number of seeds per plant, weight of 100 seed, and  very low for number of larvae per plant and yield per m2. Genotype Willis and KM 19 are two potential cultivars to be chosen as a parent to develop resistant cultivars to soybean pod borer. Keywords: soybean, variance components, heritability, genotype, resistant to soybean pod borer